Analisis Arah Kiblat Masjid Sigi Lamo Kesultanan Ternate - Sitti Nurchalifa Umaternate; Asep Ramdan Hidayat (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Mosques occupy an important position in the life of Muslims, not only in ritual worship, but also in various aspects of Muslim life. The Sultanate of Ternate is one of the four sultanates in North Maluku. Evidence of the existence of the Sultanate of Ternate is the existence of the Sultanate Mosque, one of the oldest and largest Sultanate mosques in the Sultanate of Ternate is Sigi Lamo which keeps a history of Islamic civilization and culture that still stands today. Until now, the mosque is still standing and has become the center of life for Muslims in Ternate, as a reference in fostering customs, culture and religion. The direction of the Qibla which is part of the valid requirements of prayer is an important thing in carrying out prayer services. Sigi Lamo which is a historical mosque, in determining the direction of the Qibla has been established since its inception. The direction of the Qibla of the Sigi Lamo Mosque in the Sultanate of Ternate has not changed since its inception until now, because of the sacredness of the mosque. Therefore, the author wants to examine the accuracy of the direction of the Sigi Lamo Qibla and in view of the fiqh facing the Qibla and the culture of the Ternate people. This study used a qualitative research method with a descriptive analysis approach. The purpose of this study was to determine the accuracy of the Qibla direction of the Sigi Lamo Mosque in the Sultanate of Ternate and its relationship with Fiqh. The results showed that the direction of the Qibla of the Sigi Lamo Mosque in the Sultanate of Ternate deviated from the direction of the Qibla by 20 ° 24'10